Alvin Plantinga: conoscenza religiosa e naturalizzazione epistemologica - Di Stasio, Margherita (Studi e saggi, 2011)
At least in Europe, Plantinga is better known as a philosopher of religion than as an epistemologist. This reconstruction of his work places him in broader contemporary debates on various subjects, from reliabilism to Darwinism in contraposition to creationism. The image of Plantinga that emerges is the very striking one of a thinker who, despite the intention to elaborate an epistemological theory that was declaredly confessional, has produced contributions that are of considerable interest for epistemology as a whole.